Selective removal of As(III) using magnetic graphene oxide ion-imprinted polymer in porous media: Potential effect of external magnetic field. Issue 4 (August 2021) - Chi, Zifang; Zhu, Yuhuan; Liu, Wanting; Huang, Huazheng; Li, Huai
Abstract: A novel surface-ion-imprinted polymer (IIP) was prepared using As(III) as template, and Fe3 O4 /GO as support. Adsorption behavior was studied. The fitted maximum adsorption capacity of MGO-As(III)-IIP was 49.42 mg/g.MGO-As(III)-IIP showed stable dispersive properties and great reusability in solution with an adsorption efficiency of 75% after five cycles of regeneration and reuse. MGO-As(III)-IIP indicated high selectivity under the presence of other competitive components. The binding characteristics of imprinted polymers were evaluated with the Scatchard model. Simulated column experiments with different material concentrations showed the effect of the sustained adsorption of As(III) in aquifers and the migration and residue of MGO-As(III)-IIP under external magnetic field. The adsorption effects of MGO-As(III)-IIP on 10 PV arsenic-contaminated water with a concentration of 2 mg/L were 49.76%, 68.57%, 80.74%, and 84.54%, and the recycling efficiency reached 27.1%, 34.5%, 41.1%, and 49.8%. Compared with the previous materials, the removal efficiency is greatly improved. MGO-As(III)-IIP has great potential to be used as a mobile and recyclable material for in-situ treatment of As(III) in groundwater. Graphical Abstract: ga1 Highlights: A magnetic ion-imprinted polymer was prepared for selective adsorption of As(III). Magnetic As(III) ion-imprinted polymers showed very high stability and reusability. Polymers showed highly selectivity for As(III) in presence of other competitive components. Adsorption mechanism was validated by XPS characterization. Magnetic field could enhance As(III) adsorption, migration and residue of polymers.